Design and Simulation of Dipole Patch Antenna using Graphene Sheet Substrate for UHF-RFID Application - Zamil N.; Ripin N.; Ansari M.N.M.; Jalil Y.E.; Nordin N.A.; Abdullah I.; Yahya Z.; Aziz A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Dipole antennas; Graphene; Microstrip antennas; Mobile antennas; Natural frequencies; Slot antennas; Design and simulation; Graphene sheets; Meander line; Miniaturization techniques; Patch; Patch antenna designs; Pure epoxy; RFID applications; RFID-tag; UHF RFID; Radio frequency identification (RFID)